A study on the elementary school students' mathematics self concept - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2014)
Mathematics self-concept, which can be defined as student ratings of their skills, ability; enjoyment and interest in mathematics, is seen as an important factor in mathematics education. In this context, the purpose of this study was to investigate the elementary school students' mathematics self-concept levels regarding their grade level and gender. Relational survey method was used in this study. The research sample were composed of 281 students, determined by randomly from in a primary and a secondary school in Istanbul in the spring term of 2013-2014 academic year. Data were collected using the Self-Description Questionnaire-I developed by Marsh (1992) and adapted into Turkish by Yildiz and Per (2008). Analysis of variance (One-way ANOVA) and independent sample t-test were employed to analyze data. The results of the analyses indicate that there is a statistically significant difference between elementary school students' mathematics self-concept levels based on their grade levels. Furthermore, there was a significant difference in elementary school students' mathematics self-concept levels points of view gender. In the light of the findings of this study, the researchers have developed suggestions. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: mathematics; mathematics self-concept; mathematics education; elementary; ACHIEVEMENT; VALIDATION